Non-operative treatment of splenic injury in patients with blunt abdominal trauma - Wani, Munir Ahmad; Shah, Mudassar; Malik, Ajaz Ahmad (International Surgery Journal, 2016)
Background: Few decades back splenectomy was the sole treatment for splenic injury. But with the recognition of OPSI and mortality related to it, attempts have been made to preserve the spleen whenever possible. Patients with blunt abdominal trauma and splenic injury can be treated non-operatively in selected cases. Methods: One hundred (100) patients of blunt abdominal trauma with splenic injuries were treated non-operatively between 2013 and 2015. Patients were between 18 and 60 years of age and 95 were males. Patients having signs of peritonism or free intraperitoneal fluid on FAST were subjected to contrast CT abdomen. Patients having life threatening extra-abdominal injuries were excluded from the study. Similarly, patients having Grade V splenic injury, pneumoperitoneum or contrast extravasation were operated and hence excluded from study. The patients were monitored, transfused blood when necessary and discharged when stable enough. Results: We had 20 Grade I, 26 Grade II, 44 Grade III and 10 Grade IV splenic injuries. Associated thoracic injuries were seen in 20 patients, orthopaedic injuries in 13 patients, head/maxillofacial injuries in 4 patients and other abdominal injuries in 22 patients. The hospital stay was between 5 and 20 days. 23 patients needed blood transfusion. There was no operative intervention and no mortality in 100 patients. Conclusions: Patients with splenic injury who are haemodynamically stable can be effectively managed non-operatively under meticulous monitoring and ever readiness for operative intervention if need arises. Saving spleen saves the patient from laparotomy and some life threatening infections.